Abbreviate and insert? Message length, addressee and non-standard writing in Italian mobile texting and Facebook. Issue 2 (3rd July 2017) - Zelenkauskaite, Asta
ABSTRACT: This study analyses non-standard typography (NST) (abbreviations and insertions) and its relationship to the message length, the addressee in two modes: Facebook and mobile texting SMS in the same context, i.e., messages sent by listeners of an Italian radio station. The analysis of NST showed that, if not accounted for length, there were more abbreviations in SMS messages and more insertions in Facebook messages. Nevertheless, when accounting for length, addressee analysis and non-standard typography comparison between shorter and longer messages has revealed a more nuanced picture. While Facebook messages concurrently included insertions and abbreviations, however, such use of NST has not influenced the message length: no differences were found between actual or hypothetical length neither in Facebook, nor in SMS. Furthermore, addressee analysis has revealed that listenerto-listener messages contained more NST, compared to the ones where listeners addressed their messages to the radio station, indicating a perceived differentiation between interlocutors marked via NST. These findings indicate users' adaptations to technological length constraints, addressee awareness or an overall sensitivity towards the genre of interactive message exchange via this radio broadcaster. In other words, listeners might have (intuitively) developed a perceived optimal message length for both modes of communication.